Faculty of pharmacy, UiTM shines with 3 place victory at the 18 MYPSA national sports carnival - Syazwan, Sofiyah Ahmad; Jahidin, Aisyah Hasyila; Othman, Ahmad Azani; Affandi, Nur Aina Asyifa (Faculty of Pharmacy, 2025)
This annual sporting extravaganza is more than just a competition. It is a celebration of fitness, friendship, and unity within the pharmacy student community nationwide. Participants from universities across Malaysia gathered to showcase not only their athletic skills but also the team spirit and camaraderie that define future pharmacy leaders.